A review of the implication of hypoxanthine excess in the physiopathology of Lesch–Nyhan disease. (1st December 2016) - Torres, R. J.; Prior, C.; Garcia, M. G.; Puig, J. G.
ABSTRACT: Lesch–Nyhan disease is caused by HGprt deficiency, however, the mechanism by which enzyme deficiency leads to the severe neurological manifestations is still unknown. We hypothesized that hypoxanthine excess leads, directly or indirectly, through its action in adenosine transport, to aberrations in neuronal development. We found that hypoxanthine diminishes adenosine transport and enhances stimulation of adenosine receptors. These effects cause an imbalance between adenosine, dopamine, and serotonin receptors in HGprt deficient cells, and cells differentiated with hypoxanthine showed an increase in dopamine, adenosine and serotonin receptors expression. Hypoxanthine deregulates early neuronal differentiation increasing WNT4 and EN1 gene expression.